Cogs in the Machine: The Experiences of Female Munitions Workers and Members of the Australian Women's Land Army in South Australia, 1940–45. (3rd July 2018) - Harris, Rachel; Sendziuk, Paul
Abstract : Mobilisation on the Australian 'home front' during the Second World War enabled some women to move temporarily into employment usually reserved for men, and to earn significantly higher wages than they were accustomed to, but the benefits of this have been often overstated. Focusing on South Australian women in the city and rural areas who took up the new working opportunities — in munitions factories and the Australian Women's Land Army in particular — this article demonstrates that relatively few women were entitled to higher wages, such wages were lower and paid later in South Australia than in other states, and that working conditions were unattractive and often dangerous. At the war's end, the social imperative to marry and raise children, coupled with demands that they give up their place for male workers, then saw many women return to domesticity or less-rewarded and lower status 'female occupations'.